PERAN DAN TANGGUNG JAWAB PERGURUAN TINGGI DALAM PERMENDIKBUDRISTEK NOMOR 30 TAHUN 2021 (Studi Analisis Melalui Perspektif Ilmu Perundang-Undangan) - Laurencia Clayra Skandi Suwandari, (2023)
Sexual violence is a criminal act that is rampant even in the world of education. Therefore, the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) issued Permendikbudristek Number 30 of 2021 about Prevention and Handling of Sexual Violence in order to prevent and protect all academicians from sexual violence. This study aims to find out and examine the urgency of the establishment of Permendikbudristek Number 30 of 2021, especially through the perspective of the formation of laws and regulations, as well as the role and responsibility of universities in their participation in overcoming sexual violence in universities. The research was conducted using normative juridical methods through a statute approach, a philosophical approach and a sociological approach. This research shows that Permendikbudristek Number 30 of 2021 has formal defects that are not in accordance with the formation of laws and regulations, which contains material criminal content that should not be regulated by a Ministerial Regulation.